Impact of different fertilizers on some phytochemical constituents and biological activities of Beta vulgaris L. leaves - farouk, Ghada; Mostafa, Horia (International Journal of Basic and Applied Sciences, 2017)
Red beet leaves are used in some countries in salads, while others consider them as leftover. Our goal is to conduct field experiment, for two seasons, to evaluate the effect of various combinations of (organic, chemical and bio-/yeast) fertilizers and different harvest dates on some leaves growth parameters, biocostituents and biological activities. The applied fertilizers significantly increased most of the growth parameters compared to control and highest values were produced by 100%chemical fertilizer (2), followed by treatments of 75%biofertilizer (4) and 75%yeast (8). Highest chlorophyll (a&b) and carotenoids contents were recorded by treatments 2, 4 and 8, particularly those of the second stage. Most of the studied fertilizers significantly increased betanin and polyphenolic contents compared to control and highest values were attained by treatments 4 and 8. Maximum values of betanin and polyphenols were reached in the first and third stages, respectively. Additionally, highest antioxidant activity was afforded by leaves of treatments 4 and 8, whereas leaves of treatment 4 provided a broader antimicrobial activity than control. Moreover, the highest cytotoxic activity was exerted by leaves of treatment 4. Finally, it is recommended to harvest beet leaves at the appropriate stage to obtain high growth values and reasonable percentages of bioactive metabolites.